2021
DOI: 10.1016/s2468-2667(21)00158-4
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation patterns among children exposed to childhood adversity: a population-based cohort study of half a million children

Abstract: Background Children who are exposed to adversities might be more susceptible to disease development during childhood and in later life due to impaired physiological and mental development. To explore this hypothesis, we assessed hospitalisation patterns through childhood and into adult life among those exposed to different trajectories of adversities during childhood.Methods For this population-based cohort study, we used annually updated data from Danish nationwide registers covering more than half a million … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 29 publications
2
29
1
2
Order By: Relevance
“…Therefore, our findings complement population-level reports from the Danish Life Course Cohort Study, which used datadriven approaches (eg, trajectory analyses) to group individuals into higher and lower adversity groups. 86,87 Our prevalence estimate for any child maltreatment or maternal IPV (3%) is over ten times higher than previous estimates in nationwide studies of hospital admissions (eg, <0•1%), 19 and higher than previous studies using primary care data (eg, 1•8% for child maltreatment). 88 Estimates for the more prevalent ACEs, such as maternal substance misuse and maternal mental health problems, were also higher than previous primary care studies assessing mothers or children in isolation.…”
Section: Discussioncontrasting
confidence: 64%
“…Therefore, our findings complement population-level reports from the Danish Life Course Cohort Study, which used datadriven approaches (eg, trajectory analyses) to group individuals into higher and lower adversity groups. 86,87 Our prevalence estimate for any child maltreatment or maternal IPV (3%) is over ten times higher than previous estimates in nationwide studies of hospital admissions (eg, <0•1%), 19 and higher than previous studies using primary care data (eg, 1•8% for child maltreatment). 88 Estimates for the more prevalent ACEs, such as maternal substance misuse and maternal mental health problems, were also higher than previous primary care studies assessing mothers or children in isolation.…”
Section: Discussioncontrasting
confidence: 64%
“…Research highlights how exposure to ACEs is associated with a higher prevalence of mental disorders (e.g. PTSD, anxiety, depressive and conduct disorders) in childhood and adolescence that may persist into adulthood (Hughes et al ., 2017 ; Baldwin et al ., 2021 ; Rod et al ., 2021 ). A systematic review and meta-analysis on the effects of multiple ACEs on health including 37 studies and a total of 253 719 participants, for example, reported how having multiple ACEs (up to age 16–18) is a major risk factor for several health conditions.…”
Section: Aces As Social Determinants Of Mental Healthmentioning
confidence: 99%
“…Many effects of low SES on the composition of the microbiota are difficult to disentangle from the effects of stress, but it is clear that childhood adversity is associated with increased mortality in later life ( 180 ), and it is likely that the microbiota is involved. For example, separating rat pups from their mothers in the neonatal period had long-term effects on the biodiversity of their microbiomes that persisted into adulthood ( 164 ), and stressing adult rodents also causes an altered microbiome ( 181 ).…”
Section: Ses-linked Factors That Further Distort the Microbiotamentioning
confidence: 99%